The Influence of Self-Esteem and Psychological Flexibility on Medical College Students' Mental Health: A Cross-Sectional Study - Guo, Jiamei; Huang, Xin; Zheng, Anhai; Chen, Wanjun; Lei, Zhongli; Tang, Chenglu; Chen, Hongyu; Ma, Hongyan; Li, Xuemei (Frontiers in Psychiatry, 2022)
Mental health problems has become a major public health issue among medical students. Self-esteem and psychological flexibility were important associated factors for mental health, but their relationship has not been discussed in medical students. This study aimed to assess the status of mental health problems among medical students and cover whether psychological flexibility has a mediating role in the effects of self-esteem on the top three most common issues. A total of 810 undergraduate students from 18 classes comprised the sample. Participants completed sociodemographic questionnaire, Symptom Checklist- 90-revised (SCL-90-R), Self-esteem Scale (SES) ,Acceptance and Action Questionnaire 2nd Edition (AAQ-Ⅱ), Cognitive Fusion Questionnaire(CFQ-F). Univariate analysis and logistic regression analysis was used to determine the relationship among the top three most common symptoms, self esteem, psychological flexibility, and participants’ characteristics. The mediating effect of psychological flexibility was detected by bootstrap method. 57.8% of the medical undergraduate students reported at least one dimension positive psychiatric symptoms of the 9 psychological symptom dimensions assessed by the SCL-90-R and 13.8% of students had moderate or more severe symptoms. Obsessive- compulsiveness, interpersonal sensitivity, and depression were the top three most common symptoms among the medical students. For female students, the scores of depression and obsessive-compulsiveness were significantly higher(P＜0.05). And the scores of obsessive-compulsiveness, interpersonal sensitivity, and depression were significantly higher among the students from higher grade and with bad relationship with roommates (P＜0.05). Meanwhile, obsessive-compulsiveness, interpersonal sensitivity, and depression were negative associated with the self-esteem and psychological flexibility. Almost 50% effects of self-esteem on these three symptoms in medical students exert indirect effects through psychological flexibility. In China, psychological distress was very common among medical university students, and obsessive-compulsiveness and interpersonal sensitivity are more common than depression. Both low self esteem and low psychological flexibility were risk factors for these top three symptoms and psychological flexibility is a mediating factor between self-esteem and mental health.